1982
DOI: 10.1152/ajpgi.1982.242.4.g380
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of intestinal goblet cell secretion. II. A survey of potential secretagogues

Abstract: The factors that regulate the rate of mucus secretion in intestinal goblet cells are only partially defined. Autoradiographic and ultrastructural studies demonstrated that muscarinic cholinergic agents accelerate the exocytosis of mucus from goblet cells in the crypts throughout the small and large intestine, both in vivo and in mucosal organ culture. The present study seeks to identify other factors that may alter mucous secretory rates. Mucosal explants were exposed to potential secretagogues and inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 0 publications
1
54
1
Order By: Relevance
“…Goblet cells secrete mucin via an unregulated constitutive pathway that is dependent on the continuous movement of mucin granules from the Golgi apparatus to the apex of the cell and by a regulated process dependent on the sudden release of mucin from granules. This regulatory process is controlled by a wide variety of stimuli, including nerve activation and inflammatory mediators (6,31,33). In this study, we clearly demonstrated that leptin is one of these stimuli.…”
Section: Discussionsupporting
confidence: 53%
“…Goblet cells secrete mucin via an unregulated constitutive pathway that is dependent on the continuous movement of mucin granules from the Golgi apparatus to the apex of the cell and by a regulated process dependent on the sudden release of mucin from granules. This regulatory process is controlled by a wide variety of stimuli, including nerve activation and inflammatory mediators (6,31,33). In this study, we clearly demonstrated that leptin is one of these stimuli.…”
Section: Discussionsupporting
confidence: 53%
“…Originally, it was thought that goblet cells extrude a single mass of mucus through a break in the apical plasma membrane (40-45). Subsequent studies of intestinal goblet cells by Specian and Neutra (46) have demonstrated compound exocytosis which can be evoked by a variety of secretagogues (47). A similar sequence has been observed in goblet cells of the cat trachea (Tandler, B., unpublished observations).…”
Section: Discussionmentioning
confidence: 62%
“…Although great advances have been made in recent years in identifying distinct mucin genes and types of mucins, most studies of mucus release have focused on histological changes associated with mucus-secreting cells and the thickness of the extrinsic mucus layers on epithelia (26,(30)(31)(32).…”
Section: Mucus Stimulationmentioning
confidence: 99%